Water Distribution Network Reliability Assessment beyond the Resilience Index - Joaquim Sousa; João Muranho; Marco Bonora; Mario Maiolo (Engineering Proceedings)
Water distribution network design must consider cost and reliability, with reliability being complex to assess, involving mechanical, hydraulic, and water quality aspects. Current metrics like flow entropy and resilience index have known flaws. This paper presents a new index, addressing the known weaknesses of the original resilience index and including critical network features in reliability assessment. The new proposed index introduces a novel pressure surplus threshold, setting more realistic pressure limits in operational management.